Mechanisms of Ischemic Heart Disease Development in Type 2 Diabetes Patients Based on Renal Function - Georgii B. Mankovskyi; Yevhen Yu. Marushko; Yana Yu. Dzhun; Oleksandr S. Stychynskyi (Ukrainian Journal of Cardiovascular Surgery, 2024)
Ischemic heart disease (IHD) remains a leading cause of mortality and disability in Ukraine and globally, primarily due to stenosing atherosclerosis of the coronary arteries. Type 2 diabetes mellitus (T2DM) is a significant factor accelerating atherogenesis, alongside with chronic kidney disease. Investigating the causes of myocardial ischemia in patients with IHD, T2DM, and cardio-renal-metabolic syndrome requires further exploration.The aim. To investigate the prevalence of various causes of myocardial ischemia in patients with IHD and T2DM based on renal function.Materials and methods. The study involved 103 patients with IHD and T2DM examined at the Ukrainian Children’s Cardiac Center in 2023. Participants were divided into two groups: 52 with IHD, T2DM, and stage 3A or higher chronic kidney disease; and 51 with IHD and T2DM. All the patients had angina pectoris; myocardial ischemia was confirmed in 47 (45.6%) cases by stress echocardiography and in 56 (54.4%) via exercise electrocardiography testing. Echocardio graphy with intravenous dipyridamole was performed to diagnose coronary microvascular dysfunction and determine coronary flow reserve. Renal function was assessed using estimated glomerular filtration rate (eGFR) based on the CKD‑EPI score.Results. Demographic indicators were comparable: 32 (61.5%) / 20 (38.5%) men/women in the clinical group and 30 (58.8%) / 21 (41.2%) in the control group (p > 0.05); the mean age was 56.3 ± 0.3 and 57.1 ± 0.4 years (p > 0.05). Patients with eGFR <60 ml/min/1.73 m2 had a lower frequency of single-vessel disease and a higher proportion of threevessel disease compared to those with eGFR ≥60 ml/min/1.73 m2. In all patients without significant coronary artery disease, coronary flow reserve was less than 2. In the clinical group, significant atherosclerotic lesions were the cause of IHD more frequently (86.5%) compared to the control group (64.7%), while microvascular angina had a significantly higher frequency (13.5% vs. 35.3%).Conclusion. In patients with IHD, T2DM and reduced glomerular filtration rate (eGFR <60 ml/min/1.73 m2), more aggressive coronary artery disease was observed. Consequently, the proportion of microvascular dysfunction as a cause of myocardial ischemia was higher in patients with eGFR ≥60 ml/min/1.73 m2. Therefore, a comprehensive approach in managing patients with comorbid conditions becomes an even more relevant topic for further research aimed at improving prognosis.